Protective hydrogel to heal post maxillofacial surgery paresthesia? - Ricardo Grillo; Gabriel Pedrosa; Rubens G. Teixeira (Elsevier, 2021)
This paper aims to relate a beneficial secondary effect in using protective antibiotic-impregnated hydrogel over maxillofacial surgery fixation. Twelve patients were submitted to maxillofacial surgery. All of them were submitted to stable internal fixation, and a layer of protective hydrogel was installed over plates and screws to prevent infection. There is no infection case, but as an essential and beneficial secondary effect, all patients have reported healing of alveolar inferior nerves paresthesia sooner as expected. The protective hydrogel could be useful not only in cases of infection prevention but as a paresthesia prevention method.